The AKT inhibitor, MK-2206, attenuates ABCG2-mediated drug resistance in lung and colon cancer cells - Gao, Hai-Ling; Cui, Qingbin; Wang, Jing-Quan; Ashby, Charles R.; Chen, Yanchun; Shen, Zhi-Xin; Chen, Zhe-Sheng (Frontiers in Pharmacology, 2023)
The overexpression of ATP binding cassette (ABC) transporters, ABCB1 and ABCG2, are two of the major mediators of multidrug resistance (MDR) in cancers. Although multiple ABCB1 and ABCG2 inhibitors have been developed and some have undergone evaluation in clinical trials, none have been clinically approved. The compound, MK-2206, an inhibitor of the protein kinases AKT1/2/3, is undergoing evaluation in multiple clinical trials for the treatment of certain types of cancers, including those resistant to erlotinib. In this in vitro study, we conducted experiments to determine if MK-2206 attenuates MDR in cancer cells overexpressing the ABCB1 or ABCG2 transporter. The results showed that MK-2206 significantly increased the efficacy of anticancer compounds that were substrates for the ABCG2 but not the ABCB1 transporter. MK-2206 alone (0.03-1 μM) did not significantly alter the viability of H460/MX20 and S1-M1-80 cancer cells, which overexpress the ABCG2 transporter, compared to cells incubated with vehicle. However, MK-2206 (0.3 and 1 μM) significantly increased the anticancer efficacy of mitoxantrone, SN-38 and topotecan, in H460/MX20 and S1-M1-80 cancer cells, as indicated by a significant decrease in the IC50 values, compared to cells incubated with vehicle. MK-2206 significantly increased the basal activity of the ABCG2 ATPase (EC50 = 0.46 μM) but did not significantly alter its expression level and sub-localization in the membrane. The molecular modeling results suggested that MK-2206 binds to the active pocket of the ABCG2 transporter, by a hydrogen bond, hydrophobic interactions and π-π stacking. In conclusion, these in vitro data indicated that MK-2206 surmounts resistance to mitoxantrone, SN-38 and topotecan in cancer cells overexpressing the ABCG2 transporter. If these results can be translated to humans, it is possible that MK-2206 could be used to surmount MDR in cancer cells overexpressing the ABCG2 transporter.